NILAI-NILAI PENDIDIKAN AKHLAK DALAM ALQURAN (Studi Analisis Kisah Nabi Adam as Pada Q.S. al-Baqarah: 30-39) - Agus Salim, Achyar Zein, Syamsu Nahar (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2018)
Abstract: As a majority Muslim country, Indonesia is far from Islamic values. One of the problems faced isthe moral crisis. One story of moral education is in the memorial of the prophet Adam’s story in Q.S alBaqarah: 30-39 with the phenomenon of moral shift in human life. The purpose of this study is to examinethe views of mufassir, understanding, and describe the implementation of moral education values containedin Q.S al Baqarah: 30-39. This research is library research and qualitative approach. Data weretaken from related books and commentaries, and analyzed data using tafsir tahlili method. The results ofthis study indicate that: the values contained in Q.S al Baqarah: 30-39 are humble, proud prohibition,prohibition of envy, and forgiving. Implementation of a humble attitude as the main foundation in understandingand mastering science, the arrogant prohibition when it has any merit in order not to use it inpride let alone degrading others, the spiteful embedded in the self makes discomfort when looking at theperson of a higher position, the forgiving nature that in the end muffling any pent-up liver disease. Actualizationof moral education will be realized by prioritizing the positive traits taken in Q.S al Baqarah: 30-39.Sebagai negara muslim mayoritas, Indonesia jauh dari nilai-nilai keislaman. Salah satu problem yangdihadapi adalah krisis akhlak. Salah satu kisah pendidikan akhlak ada dalam peringatan kisah nabiAdam as dalam Q.S al Baqarah: 30-39 dengan fenomena pergeseran moral di dalam kehidupan manusia.Tujuan penelitian adalah menelaah pandangan mufassir, memahami, dan mendeskripsikan implementasinilai-nilai pendidikan akhlak yang terkandung dalam Q.S al Baqarah: 30-39. Penelitian ini menggunakanlibrary research dengan pendekatan kualitatif. Data diambil dari buku-buku dan tafsir yang berkaitan,dan menganalisis data menggunakan metode tafsir tahlili. Hasil penelitian ini menunjukkan bahwa: nilaiyang terkandung dalam Q.S. al Baqarah ayat 30-39 adalah rendah hati, larangan sombong, larangandengki, dan pemaaf. Implementasi sikap rendah hati sebagai pondasi utama dalam memahami danmenguasai keilmuan, larangan sombong ketika mempunyai kelebihan apapun agar tidak memanfaatkannyadalam kesombongan apalagi merendahkan orang lain, sifat dengki yang tertanam dalam diri membuatketidaknyamanan ketika melihat orang yang kedudukannya lebih tinggi, sifat pemaaf yang pada akhirnyameredam segala penyakit hati yang terpendam. Aktualisasi pendidikan akhlak akan terealisasi denganmengutamakan sifat-sifat positif yang diambil dalam Q.S al Baqarah: 30-39.